Impact of Customer Relationship Management Practices on Customer Behavior in Restaurant Industries of Bangladesh - Sharmen, Sayma (International Journal of Marketing Research Innovation, 2018)
The purpose of this paper is to provide proof that consumer relationship management can help to influence customer behavior in restaurant industries (Gloria Jean’s, Olympia palace restaurant) and help them to maintain profitable loyal consumers. Data were collected using semi-structured questionnaire and both qualitative and quantitative research methodology was used. There were 60 respondents and the research questionnaire is based on 7 point Likert scale. A key finding was that CRM activities help to develop good relationship with consumers and increase their satisfaction level. Consumers who visited these restaurants often prefer these restaurants over other restaurants. This research was conducted within specific restaurants. The sample size could have been bigger. To further explore the application of CRM in restaurants and the connection of profitability and loyalty with CRM there should be more explicit research. The fact that consumer relationship management is a part of effective and efficient management system and can be essential to ensure retention of consumers. The paper is unique in that we provide evidence of the importance of consumer relationship management in restaurant business where most often no CRM activities is conducted.